Historical Perspective. Issue 2 (April 2016) - Tarran, Brian
Abstract : An interview with Stephen Stigler, historian and Ernest DeWitt Burton Distinguished Service Professor at the Department of Statistics of the University of Chicago Abstract : An interview withStephen Stigler, historian and Ernest DeWitt Burton Distinguished Service Professor at the Department of Statistics of the University of Chicago